Feeding and digestion with bivalves - Deslous-paoli, Jean-marc (Actes du colloque, Nutrition in Marine Aquaculture, FAO-MEDRAP. A. Bruno (Ed.), Lisbon 20-30 Octobre 1986, pp 145-198, 1986)
On the contrary to the U. S. where they represent but 4.6% of the total marine production , mollusc, principally bivalves, can no longer be considered as a marginal production. In France, 100 000 ton of oysters, 98% of which is represented by Crassostrea gigas (Héral & al., 1985) and 85 000 ton of mussels (Mytilus edulis, Mytilus edulis galloprovincialis) (Dardignac, 1985) are produced yeraly. Elsewhere, new rearings are being developed, such as pectinidae and Ruditapes philippinarum, on the Atlantic and Mediterranean coasts. The species presently cultured, some of which dependiing only on natural collections (Crassostrea gigas, Mytilus edulis, Mytilus galloprovincialis while others depend on hatchery production, either partially Crasssotrea gigas in the U. S., Pecten maximus, Ostrea edulis, or totally (Ruditapes philippinarum, Crassostrea virginica, Argopecten irradians. In addition, the development in laboratories of mollusc strains with higher growth potential, or showing more resistance to disease, will be derived exclusively from hatchery productions.